Fundo de investimento imobiliário: metodologia para subsidiar o investidor a formar uma carteira eficiente - Albernaz, Álvaro Germano (2015)
This work intends to subsidize the real estate investment funds investor in choosing a FII investment portfolio in order to obtain performance at or above the industry benchmark (IFIX). Such a grant is made initially by methodology which considers the concept of Efficient Portfolio (Risk / Return) proposed by Markowitz, can work together with the dimension of the concept of Behavioral Finance, led by Daniel Kahneman, constituting the investor’s orientation bases. We add the methodological approach to the indications suggested by Bazerman and Moore, in the decisionmaking process that reduces the effects of heuristics and viésis. To start the way the investor responds to questionnaire of 5 questions that aims to classify the degree of ’capacity and tolerance ―by the IFI prod-uct. From their responses the investor will be referred to a‖ cluster ―of funds, classified according to the perception of retail investor, according to the complexity of analyzing the background. Selected FIIs with potential for application, bring the investor as an ‖Ranking― of the funds in question answering three questionnaires that motivate the expansion of its research in the following dimensions :. (i) Capacity of the fund, (ii) on the (s) Active (s) of the fund, and (iii) of the Income Generation of FII Complementing the creation of ‖Ranking― is also considered its Anchor decision, ie, the main investor reason to choose each selected fund. Finally, we use the concept of Markowitz to identify the most efficient Portfolio considering the ‖Ranking' of the investor, with the EXCEL package with the tool SOLVER. The results of that portfolio were higher than the industry benchmark (IFIX), demonstrating technically than using appropriate tools and establishing a path to guide the investor research in finding structural information you can build an efficient portfolio that helps the his applications long term.